Exchange Rate Fluctuations, Institutional Quality and Foreign Direct Investment in Nigeria - Akintola, Francis A.; Ogbebor, Peter I.; Fatade, Fisayo A (Advances in Social Sciences Research Journal, 2026)
Foreign Direct Investment (FDI) remains a critical source of foreign exchange earnings and economic growth in Nigeria. Despite various policy initiatives by the Federal Government and the Central Bank of Nigeria (CBN) to stabilize the Naira against major global currencies, as well as the efforts of the Economic and Financial Crimes Commission (EFCC) to curb corruption, FDI have remained volatile. This persistent instability has raised concerns about the potential influence of exchange rate fluctuations and weak institutional quality on FDI performance in the country. This study therefore examined the effect of exchange rate fluctuations and institutional quality on foreign direct investment in Nigeria between 1996 and 2024. This study employed ex post facto research design to examine the effect of exchange rate fluctuations and institutional quality on foreign direct investment in Nigeria. Time series secondary data were obtained from CBN statistical bulletin. Descriptive and inferential (multiple regression and granger causality) statistics at 5 per cent level of significance. Empirical findings revealed that exchange rate fluctuations and institutional quality jointly exert a significant negative effect on FDI (Adj. R² = 0.80; F(6,29) = 19.04; p < 0.05). Specifically, exchange rate fluctuations showed a negative but insignificant impact on FDI (α₁ = -0.00, t = -1.83, p > 0.05), while institutional quality exhibited a negative and significant influence (α₂ = -0.07, t = -3.01, p < 0.05). The combined exchange rate fluctuations and institutional quality also had negative and significant effect on FDI (α₃ = -0.00, t = -3.25, p < 0.05). The study concluded that both exchange rate fluctuations and weak institutional quality significantly affect the foreign direct investments in Nigeria. It recommended the implementation of credible exchange rate management strategies and institutional reforms that promote transparency, accountability, and the rule of law to foster a more stable and investment-friendly environment.